Listening to young nonbelievers and Catholics. Italian focus group on spirituality and faith in God - Galatolo, Cecilia (Church, Communication and Culture, 2025)
This case study explores the spiritual and moral perceptions of Italian youth through two focus groups – one composed of non-believers and the other of Catholics – conducted in Rome in April 2024. The research complements the broader Footprints survey, which examined religious beliefs among young people aged 18–29 across eight countries. Participants discussed themes such as spirituality, belief in God, conscience, sin, moral consistency, and controversial ethical issues like abortion and pornography. Findings reveal that both non-believers and Catholics experience a strong desire for spirituality, yet are heavily influenced by secular cultural trends. Non-believers demonstrate a thoughtful, self-critical approach to their beliefs and maintain openness to transcendence without aligning with traditional Christian concepts. Conversely, Catholics often exhibit limited theological knowledge and struggle to articulate their faith, frequently treating it as a set of inherited opinions rather than personally internalized convictions. Both groups reveal moral contradictions between stated beliefs and actual ethical positions. Catholics particularly show a tendency to accommodate cultural norms over religious doctrine, especially regarding issues like abortion and sexual ethics. The study highlights the need for more robust catechesis and pastoral engagement for Catholics.